Editorial: Volume 12, Número 22 (2024) - Marco Aurélio Kistemann Junior; Neil da Rocha Canedo Junior; Luciane Mulazani dos Santos (Universidade do Estado de Santa Catarina, 2024)
Edição Temática: "O uso de vídeos digitais em educação matemática: possibilidades e desafios".